1999
DOI: 10.1093/ptj/79.7.642
|View full text |Cite
|
Sign up to set email alerts
|

Cause, Prevalence, and Response to Occupational Musculoskeletal Injuries Reported by Physical Therapists and Physical Therapist Assistants

Abstract: Although PTs and PTAs are recognized to be knowledgeable in prevention and treatment of musculoskeletal injuries, they are susceptible to sustaining occupational musculoskeletal injuries because of performing labor-intensive tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
128
0
21

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 173 publications
(170 citation statements)
references
References 11 publications
21
128
0
21
Order By: Relevance
“…For example, Campo et al 14) observed that WRMD prevalence was higher in older physical therapists than in younger physical therapists. In contrast, most previous studies have reported that therapists experience symptoms before they reach 30 years of age, and the incidence rate within 5 years of graduation is high 5,9,11,12,15) . The suggested reason is that new physical therapists lack professional experience, knowledge, and techniques, and that they are rotationally dispatched to different places, thereby running a higher risk of injury 1,16) .…”
Section: Introductionmentioning
confidence: 74%
See 2 more Smart Citations
“…For example, Campo et al 14) observed that WRMD prevalence was higher in older physical therapists than in younger physical therapists. In contrast, most previous studies have reported that therapists experience symptoms before they reach 30 years of age, and the incidence rate within 5 years of graduation is high 5,9,11,12,15) . The suggested reason is that new physical therapists lack professional experience, knowledge, and techniques, and that they are rotationally dispatched to different places, thereby running a higher risk of injury 1,16) .…”
Section: Introductionmentioning
confidence: 74%
“…WRMD results in loss of work time, restriction of tasks, or transfer to a different job, thereby affecting the quality of life of the patient [2][3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Various studies show that WMSDs are common among healthcare workers [28][29][30]. Nuikka et al [31] showed that workload in primary care situations and in transporting the patient can be classified as moderately heavy, based on heart rate and relative workload.…”
Section: Temporal Aspect Of Job Demandmentioning
confidence: 99%
“…A testagem da força muscular isométrica de oito grupos musculares (flexores e extensores) do membro superior direito, mensurados por meio de dinamometria digital ou miometria (Lafayette Instruments) foi usada como indicador da manutenção de exercícios, bem como para avaliação do efeito do treinamento 10,11 . Foram coletadas três medidas de cada teste, sendo utilizada, para fins de estudo, a maior medida obtida.…”
Section: Localunclassified